Freudian Analysis of Freedom: Comparing 'Aku Perempuan' by Indah Pratama and 'The Sky is the Limit' by Rohini Vij - Tamtama, Rafael Aglis Ariya; Odelia, Risca Jovita; Bunadi, Stefanie Keren; Sriastuti, Anna (Proceedings of English Linguistics and Literature, 2024)
This comparative research analyzes the freedom of the main characters in two short stories "Aku Perempuan" by Indah Pratama and "The Sky is the Limit" by Rohini Vij using Sigmund Freud's Tripartite Personality, which consists of the Id, Ego, and Superego. The main issue in this research is how the conflict between personal desires, reality, and social norms affects the freedom of the main characters in these two stories. The aim of this research is to understand the psychological dynamics experienced by the main characters as they struggle to achieve freedom that is limited through self-realization. The researcher wants to see freedom from Id, Ego, Superego of each of the main characters of desires and what they actually want. The method used is qualitative analysis with Freud's theoretical approach, where data is obtained from the narrative texts of the two short stories. The finding of this research shows that they navigate the conflicts between the Tripartite of how the characters can get freedom through self-realization. This analysis highlights the importance of perseverance, social support, and self-determination. By understanding this, readers, especially women can achieve personal freedom within restrictive social contexts.